2000
DOI: 10.1007/s004180000214
|View full text |Cite
|
Sign up to set email alerts
|

Methods for visualizing RNA processing and transport pathways in living cells

Abstract: Recent advances in fluorescence microscopy, imaging, and probe technology provided possibilities to study the spatial and temporal distribution of RNA species in living cells. While some methods have been developed to localize all nascent or poly (A) containing transcripts others have been developed to study the in vivo distribution of specific RNA species. Irrespective of the method that has been used, the results of these studies provided important information concerning the localization and the cellular tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 58 publications
1
78
0
3
Order By: Relevance
“…These approaches include microinjection of fluorescent RNA, in vivo hybridization of fluorescent oligonucleotides, and expression of fluorescent RBPs (Dirks et al, 2001;Pederson, 2001). Indirect labeling of mRNAs with GFP has been successfully applied in yeast cells and rat neurons (Bertrand et al, 1998;Rook et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These approaches include microinjection of fluorescent RNA, in vivo hybridization of fluorescent oligonucleotides, and expression of fluorescent RBPs (Dirks et al, 2001;Pederson, 2001). Indirect labeling of mRNAs with GFP has been successfully applied in yeast cells and rat neurons (Bertrand et al, 1998;Rook et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies showed the feasibility of detecting mRNAs and monitoring the transportation of RNAs in cells, the procedure for delivery of the molecular beacons through microinjection or by liposome delivery has made it difficult to apply this technology into broad research areas or into a routine clinical procedure (9)(10)(11)(12). A recent study showed that it is feasible to transfect a molecular beacon into living cells to detect doxorubicin-induced activation of p21 gene expression (13).…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of detecting intracellular mRNA has been examined in several laboratories (9)(10)(11)(12)(13). It has been shown that molecular beacons were able to visualize mRNA molecules in several human and animal cell lines after introducing into cells through microinjection or liposome delivery (9)(10)(11)14). It has also been shown that the detection limit of preformed molecular beacon/ h-actin mRNA duplexes microinjected into the cells is 10 mRNA molecules, suggesting that molecular beacon technology is a very sensitive method for detecting mRNAs in cells (9).…”
Section: Introductionmentioning
confidence: 99%
“…This backbone has been reported to increase the half-life of beacons to a period of 2 days. 19 The final p21-beacon design included the hybridization sequence in the loop structure and had a melting temperature of 53.3˚C (Fig 1C).…”
Section: Resultsmentioning
confidence: 99%